2022
DOI: 10.1002/app.52448
|View full text |Cite
|
Sign up to set email alerts
|

Textile functionalization by combination of twin polymerization and polyalkoxysiloxane‐based sol–gel chemistry

Abstract: The surface modification of textile fibers by coating with nanostructured organic–inorganic hybrid materials is presented. The hydrophobic, solvent resistant and mechanically robust coatings were produced by combining the twin monomer 2,2′‐spirobi[benzo‐4H‐1,3,2‐dioxasiline] (TM) and polyalkoxysiloxanes (silica precursor polymers) in a catalyzed polymerization process. For the application in textile finishing, both aqueous emulsions and ethanolic solutions of mixtures were developed. The precisely adjusted rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 48 publications
(113 reference statements)
0
10
0
Order By: Relevance
“…[87] SEM studies (Figure 1) confirmed that 10 containing polymers seem to raise a higher adhesion towards the reinforcement fibers involving an enhanced fiber/matrix interaction. [87] Recently, also textile functionalization by the combination of TP with 1 and polyalkoxysiloxane-based sol-gel chemistry to achieve improved adhesion and permanence and hydrophobicity was published by Kaßner et al [88] When 1 was polymerized Scheme 4. Procedure for the preparation of urethane-based twin prepolymers 8 a,b (top) and their STP with 1 to obtain hybrid materials consisting of phenolic resin, silica and dialkylsiloxane-crosslinked polyurethane (PPG = polypropylene glycol, PTMEG = polytetramethylene ether glycol, MDI = methylendi(phenylisocyanate)) (middle).…”
Section: Orthosilicates and Oxasilanesmentioning
confidence: 99%
See 4 more Smart Citations
“…[87] SEM studies (Figure 1) confirmed that 10 containing polymers seem to raise a higher adhesion towards the reinforcement fibers involving an enhanced fiber/matrix interaction. [87] Recently, also textile functionalization by the combination of TP with 1 and polyalkoxysiloxane-based sol-gel chemistry to achieve improved adhesion and permanence and hydrophobicity was published by Kaßner et al [88] When 1 was polymerized Scheme 4. Procedure for the preparation of urethane-based twin prepolymers 8 a,b (top) and their STP with 1 to obtain hybrid materials consisting of phenolic resin, silica and dialkylsiloxane-crosslinked polyurethane (PPG = polypropylene glycol, PTMEG = polytetramethylene ether glycol, MDI = methylendi(phenylisocyanate)) (middle).…”
Section: Orthosilicates and Oxasilanesmentioning
confidence: 99%
“…[88] Abrasion testing on polyester fabrics were carried out. [88] Furthermore, the authors state that the corresponding organic-inorganic hybrid coatings may open up new perspectives for the finishing of diverse textile materials and can be combined modularly with other chemically reactive reagents, for example, UV resistant additives, amino and epoxy groups to admix and fix nanoparticles, or dyestuffs. [88] Based on earlier studies on TP on hard templates, [18] Spange and coworkers used in 2017 TP for the fabrication of hierarchically structured carbon/carbon nanocomposites with adjustable porosity by applying consecutive surface polymerization of twin monomers on carbon black and silica particles, respectively.…”
Section: Orthosilicates and Oxasilanesmentioning
confidence: 99%
See 3 more Smart Citations